IRONI, PARODI, DAN PASTICHE DALAM PUISI “TANAH AIR MATA” KARYA SUTARDJI CALZOUM BACHRI (Kajian Posmodernisme) - Diyah Herawati; Else Liliani; Widyastuti Purbani (Adabiyyāt: Jurnal Bahasa dan Sastra, 2024)
This study explores the use of irony, parody, and pastiche in Sutardji Calzoum Bachri's poem Tanah Air Mata through a postmodernist lens. This research is motivated by the fact that literary works play a role in conveying deep meanings and criticisms. Sutardji, a renowned contemporary Indonesian poet, often addresses profound themes such as social injustice. This research aims to comprehensively analyze how postmodern elements are employed in the poem to critique social and political issues. Using a qualitative descriptive method, the study involves textual analysis of the poem and secondary sources. The findings reveal that irony, the most dominant element in this poem, underscores the disparity between hope and reality in the form of suffering society feels amidst Indonesia's prosperity. Parody imitates the dominant narrative in Indonesia’s national anthem lyric, and pastiche blends traditional and modern elements to create layered meanings. Moreover, intertextuality is used to analyze these elements, linking the poetic text to grand narratives and other cultural symbols, creating a dialogue that enriches meaning and inspires readers to look critically at social reality. This approach enriches the understanding of a poem entitled Tanah Air Mata and demonstrates the power of postmodern aesthetics in contemporary poetry to highlight and critique social injustices.